(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the importance of implementing the concept of national rise, the rise in society serves the stage of national rise from national revival by effectively applying the creative activities of individuals to the fields. In turn, the development of programs that serve to ensure the development of the society and the prevention of social problems are discussed.